2016
DOI: 10.1111/cea.12670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roflumilast on airway remodelling in a murine model of chronic asthma

Abstract: These results suggest that the administration of roflumilast regulates airway inflammation, AHR, and airway remodelling in a model of chronic asthma. The beneficial effects from roflumilast may be related to the SCF/c-kit pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…3 and PDE 4 inhibitors. Phosphodiesterase (PDE) 4 inhibitors have immunomodulatory effects on inflammatory cells potentially relevant to the treatment of asthma [Lipworth, 2005;Page and Spina, 2012;Kim et al 2015b]. In an allergen challenge study the oral PDE 4 inhibitor roflumilast attenuated the rise in sputum eosinophils and neutrophil numbers after the late asthmatic response [Gauvreau et al 2011].…”
Section: Cxcr2 Antagonist Cxcr2mentioning
confidence: 99%
“…3 and PDE 4 inhibitors. Phosphodiesterase (PDE) 4 inhibitors have immunomodulatory effects on inflammatory cells potentially relevant to the treatment of asthma [Lipworth, 2005;Page and Spina, 2012;Kim et al 2015b]. In an allergen challenge study the oral PDE 4 inhibitor roflumilast attenuated the rise in sputum eosinophils and neutrophil numbers after the late asthmatic response [Gauvreau et al 2011].…”
Section: Cxcr2 Antagonist Cxcr2mentioning
confidence: 99%
“…Evidence show that asthma patient can also benefit from treatment with roflumilast since it decreases airway inflammation, remodeling and hyperresponsiveness [82,83]. The results are better when combined with montelukast or ICS [82,84].…”
Section: Managementmentioning
confidence: 99%
“…Roflumilast is a selective, small‐molecule phosphodiesterase 4 (PDE4) inhibitor that has been shown to possess anti‐inflammatory and fibrotic capabilities and is the first PDE4 inhibitor approved for treatment of chronic obstructive pulmonary disease (COPD) . Selective inhibition of PDE4 increases cellular cAMP, reducing immune cell inflammatory processes including chemotaxis, activation, and degranulation, and has been shown to reduce inflammation‐induced airway remdelling Kim et al employed a mouse model of chronic asthma to determine the effect of roflumilast on the development of the manifestations of asthma (airway inflammation, remodelling [GC hyperplasia and pulmonary fibrosis], and AHR) . The authors showed that chronic intranasal exposure of ovalbumin (OVA)‐sensitized BALB/c mice with OVA administration twice a week for 3 months induced the asthma phenotype.…”
Section: Mechanisms Of Allergic Diseasementioning
confidence: 99%
“…42,43 Selective inhibition of PDE4 increases cellular cAMP, reducing immune cell inflammatory processes including chemotaxis, activation, and degranulation, and has been shown to reduce inflammation-induced airway remdelling 42,44,45 Kim et al employed a mouse model of chronic asthma to determine the effect of roflumilast on the development of the manifestations of asthma (airway inflammation, remodelling [GC hyperplasia and pulmonary fibrosis], and AHR). 46 The authors showed that chronic intranasal exposure of ovalbumin (OVA)-sensitized BALB/c mice with OVA administration twice a week for 3 months induced the asthma phenotype. Administration of roflumilast during intranasal allergen exposure significantly inhibited airway inflammation (cellular infiltration and cytokine production) and AHR.…”
Section: Inhibiting Airway Inflammation and Remodellingmentioning
confidence: 99%